Nuclear factor-κB is involved in oxyhemoglobin-induced endothelin-1 expression in cerebrovascular muscle cells of the rabbit basilar artery. Issue 12 (17th August 2016) - Cheng, Gao; Yu, Wei H.; Yan, Cong; Liu, Yao; Li, Wei J.; Zhang, Dong D.; Liu, Nan
Abstract : The present research was designed to investigate whether endothelin-1 (ET-1) secretion can be induced by oxyhemoglobin and whether nuclear factor κB (NF-κB) is involved in the regulation of ET-1 transcription in cerebrovascular muscle cells. Cerebrovascular muscle cells isolated from a rabbit basilar artery were stimulated by oxyhemoglobin (OxyHb) and ET-1 production was increased significantly in the supernatant. Inhibition of NF-κB with pyrrolidine dithiocarbamate and small interfering RNA decreased the expression of ET-1. Nuclear translocation of NF-κB and the degradation of IkB-α was observed with the stimulation of OxyHb. The supernatant obtained from cerebrovascular muscle cells stimulated by OxyHb produced contractions in arterial rings and was blocked by the ET-1 receptor antagonist (BQ-123). The time course of the OxyHb-induced contractions of the basilar artery rings correlated with the time course of the OxyHb-induced ET-1 secretion. The contraction of the basilar artery rings induced by OxyHb was attenuated when the artery rings were preincubated with pyrrolidine dithiocarbamate and SN50 (20 and 10 µM, respectively). These results indicate that cerebrovascular muscle cells may be an important source of ET-1 production after subarachnoid hemorrhage. NF-κB was involved in the expression of ET-1 and the inhibition of the NF-κB pathway may be beneficial for the treatment of cerebral vasospasm.